Analysis and Comparison of intellect and quotation relation from the Ibn Taymiyyah and Ayatollah Javadi Amoli Viewpoint - 11 11; hamid parsania (حکمت اسرا)
The correct analysis and explanation of intellect and quotation relation based on the principles and foundations of the Ibn tamiyah and Javadi Amoli thought, as representatives of the two intellectualism and text adherence movements in the field of religious knowledge, have significant Results. Ibn Taymiyyah by rigidity on texts Appearances Even in the belief principles, beleives that the reason for the difference between philosophers and theologians, is the lack of inherent authority and independence of intellect. Therefore, he say the preceding of reasonable on fixed is baseless, and the only way of true faith is to believe decisively in the Prophet. He offer a Definition for intellect, according which intellect is accident and reduces it to the limit of instinct and common Sense; by confuse of quotation with Islamic Law, Ibn Taymiyyah absolutely defending the precede of quotation on intellect;and by  acceptance of intellect multiplicity and Epistemic Relativity, he tries to solve the conflict of intellect and quotation , and  beleives the revocation of a kind of intellect does not means the revocation of the whole intellect. But Javadi Amoli By leveling up rational and traditional  knowledges,  believes Each of the intellect and quotation is confirm one another,  and by the separation of revelation from the quotation, he introduces  quotative understanding such as Rational understanding, which is vulnerable, Unprotected from the fault and right and Conflict,  And defends interpretation as a solution to the conflict of reason and quotation; Javadi considers the preceding of rational reason on Unexplained verbal reason, to be necessary. He believes the product of empirical intellect, semi-abstractintellect, abstract intellect, and pure intellect is Valid , if it is a type of dogmatization, certainty, or led to rational assurance,  And while differentiate between intellect and the conduct of the wise ( bin’ al-‘uqala’),  he consider the  Rational argument a kind of knowledge that its reliability and validity is  inherent, not fake. According to him, it is necessary to discuss the intellect, quotation and the related topics in the epistemological domain of religion, in the principles knowledge.